STRATEGI PEMASARAN PT. PKSS CABANG YOGYAKARTA DALAM MENGHADAPI PERSAINGAN - Anggun Anindya Sekarningrum (Fakultas Teknologi dan Rekayasa, 2020)
Today many companies are use outsourcing services to manage their workers. In Indonesia alone, companies engaged in outsorcing have developed rapidly. PT. Prima Karya Sarana Sejahtera (PKSS) is a private company engaged in the business of managing labor with services in the form of products and services. In Yogyakarta, outsourcing services have developed a lot. Facing intense competition in the Outsourcing business that continues to grow, competitiveness is a key factor in being able to survive and excel in existing competition. This study aims to determine how the marketing communication strategy of PT Prima Karya Sarana Sejahtera Yogyakarta Branch in the face of competition in the Yogyakarta Region. The research that will be conducted is qualitative descriptive research. In this analysis, researchers used Five Forces Analysis from Michael E Porter. The marketing communication strategy used by PT Prima Karya Sarana Sejahtera (PKSS) to deal with competition in the Yogyakarta region uses 4 P’s Marketing Mix, namely, Product, Price, Place, and Promotion.